1994
DOI: 10.2527/1994.721139x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium level affects the efficacy of supplemental microbial phytase in corn-soybean meal diets of weanling pigs1

Abstract: A 2 x 2 x 2 factorial experiment was conducted with 64 pigs (4 wk old, 8.04 +/- .50 kg BW) to determine the effect of various dietary concentrations of Ca, vitamin D, and microbial phytase (Aspergillus niger) on phytate-P utilization. A low-P, corn-soybean meal diet was supplemented with two levels of phytase (unit/gram), 750 (suboptimal) and 1,200 (optimal); of vitamin D (international unit/kilogram), 660 (normal) and 6,660 (high); and of Ca (percentage), .4 (low) and .8 (normal). Pen feed consumption and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
71
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 11 publications
11
71
1
1
Order By: Relevance
“…1). In the present study, increasing digestible P intake or plasma P coincided with decreasing plasma alkaline phosphatase; an inverse relationship similar to the one reported by Lei et al (1994). However, plasma alkaline phosphatase decreased linearly; thus, it was not used to determine a digestible P requirement.…”
Section: Discussionsupporting
confidence: 86%
“…1). In the present study, increasing digestible P intake or plasma P coincided with decreasing plasma alkaline phosphatase; an inverse relationship similar to the one reported by Lei et al (1994). However, plasma alkaline phosphatase decreased linearly; thus, it was not used to determine a digestible P requirement.…”
Section: Discussionsupporting
confidence: 86%
“…1 were older. Lei et al (1994) however, found a depressive effect of dietary Ca level on phytase activity in weanling pigs, and Liu et al (1998) showed that P utilization in growing-finishing pigs in the presence of phytase was improved at a Ca:P ratio of 1 rather than 1.5, indicating that age does not affect this response. The inhibitory effect of Ca on phytase efficacy was shown to be less at pH 2.5 than at pH 6.5; probably because of decreased solubility of the complex at the higher pH (Tamin et al 2004).…”
Section: Phosphorusmentioning
confidence: 94%
“…The efficacy of A. niger phytase in corn and soybeanmeal-based diets was mitigated at high dietary Ca:P ratios (Lei et al 1994;Liu et al 1998). Similarly, the beneficial effects of a P. lycii phytase on reducing faecal P excretion, observed when the Ca:P ratio in the diet was 1.15:1, was no longer evident when added to a diet with a ratio of 1.85:1 (Brady et al 2002).…”
mentioning
confidence: 99%
“…The action of plant (EC 3.1.3.26) [15,28,30,42]. Dietary microbial phytase supplementation can thus improve phytic-P digestive utilization and consequently reduce P pollution by animal excreta [17,18,23,37,38]. Furthermore, improved nutrient digestibility in animals fed supplemental phytase has been reported in pigs and in poultry [3,4,22,24,25,46,47].…”
Section: Introductionmentioning
confidence: 99%